2002
DOI: 10.2741/a812
|View full text |Cite
|
Sign up to set email alerts
|

Roles of TGF-beta in hepatic fibrosis

Abstract: TGF-beta has multiple profibrogenic but also anti-inflammatory and immunosuppressive effects. The balance of these actions is required for maintaining tissue homeostasis and an aberrant expression of TGF-beta is involved in a number of disease processes in the liver. In addition to its fibrogenic action leading to transdifferentiation of hepatic stellate cells into myofibroblasts, TGF-beta is also an important negative regulator of proliferation and an inducer of apoptosis. The major portion of TGF-beta is sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
475
0
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(501 citation statements)
references
References 142 publications
13
475
0
13
Order By: Relevance
“…STAT and SMAD pathways are known to be involved in the pathogenesis of liver fibrosis and inflammation, and elevated systemic and intrahepatic levels of IL-6 and TGF-␤ were found in acute and chronic liver diseases (30,31). The activation process of HSC, causing trans-differentiation of the physiologically quiescent cells to an activated myofibroblast-like cell type, is one of the key events of hepatic fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT and SMAD pathways are known to be involved in the pathogenesis of liver fibrosis and inflammation, and elevated systemic and intrahepatic levels of IL-6 and TGF-␤ were found in acute and chronic liver diseases (30,31). The activation process of HSC, causing trans-differentiation of the physiologically quiescent cells to an activated myofibroblast-like cell type, is one of the key events of hepatic fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-␤ has pleiotropic functions including fibrinogenic action leading to trans-differentiation of HSC and negative regulation of proliferation and induction of apoptosis (31).…”
Section: Resultsmentioning
confidence: 99%
“…In line, corresponding mouse models disrupted for the endoglin gene confirmed the importance of this receptor especially in TGF-␤ signaling (33)(34)(35)(36). Here, we have cloned the rat endoglin cDNA from HSC, the cell type that, upon TGF-␤ stimulation, is mainly responsible in liver for excessive formation of extracellular matrix components, resulting in hepatic fibrosis (55,71). In contrast to endothelial cells, expressing two endoglin transcript variants, denoted L-and S-endoglin, we found that rat HSC and MFB express two variants of L-endoglin most likely provoked by usage of different polyadenylation sites.…”
Section: Fig 9 Surface Exposition Of Endoglin In Hsc/mfbmentioning
confidence: 99%
“…Receptor Betaglycan-TGF-␤ is a growth factor regulating key aspects of cellular activation and transdifferentiation of HSC (55). The ligand, TGF-␤, is bound by a heterooligomeric membrane receptor complex, consisting of the signaling receptors type I and II and at least one accessory receptor betaglycan.…”
Section: Rat Hsc Express a Homolog Of Tgf-␤ Type III Familymentioning
confidence: 99%
“…Both, (TGF-β) excess and deficiency are causal for the development of fibrotic and autoimmune liver diseases respectively which can be inhibited by anti-(TGF-β) treatments like neutralizing antibodies. In the liver, (TGF-β) is a very potent profibrogenic mediator of cellular responses leading to tissue repair, ECM production, growth regulation, and apoptosis [12]. stages in cerebral blood flow and brain, and provides a way of increasing the Aβ-induced cellular stress underlying neuronal dysfunction and dementia ( Figure 3).…”
Section: Transforming Growth Factormentioning
confidence: 99%